2014
DOI: 10.1192/bjp.bp.112.125286
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness of cognitive–behavioural therapy as an adjunct to pharmacotherapy for treatment-resistant depression in primary care: economic evaluation of the CoBalT Trial

Abstract: The addition of CBT to usual care is cost-effective in patients who have not responded to antidepressants. Primary care physicians should therefore be encouraged to refer such individuals for CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 36 publications
(52 reference statements)
0
38
0
Order By: Relevance
“…Personalising the choice of treatment will be critical to more efficient use of health care resources in the future (Cuijpers et al, 2012, Hollinghurst et al, 2014, Simon and Perlis, 2010, Wallace et al, 2013. Second, we would encourage the use of observational data coupled with appropriate statistical methods to gain a better understanding of the effects of depression treatment in a routine care setting and the long-term cost-effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Personalising the choice of treatment will be critical to more efficient use of health care resources in the future (Cuijpers et al, 2012, Hollinghurst et al, 2014, Simon and Perlis, 2010, Wallace et al, 2013. Second, we would encourage the use of observational data coupled with appropriate statistical methods to gain a better understanding of the effects of depression treatment in a routine care setting and the long-term cost-effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…However at a willingness-to-pay of zero per unit of improvement, the probability is 24%. (Domino et al 2008;Lynch et al 2011;Maljanen et al 2012;Hollinghurst et al 2014). All studies included a well-defined research question, reported on the effectiveness of the programme or service concerned, identified all relevant costs and consequences for each alternative, measured costs and consequences accurately, and valued the cost credibly.…”
Section: Uk Societalmentioning
confidence: 99%
“…Only three studies reported on adjusting cost and consequences for differential timing (Byford et al 2007;Domino et al 2008;Maljanen et al 2012). Five studies did not make allowances for uncertainty in the estimation of costs ( Only three studies allowed for uncertainty in the estimation of consequences (Domino et al 2008;Lynch et al 2011;Hollinghurst et al 2014).…”
Section: Uk Societalmentioning
confidence: 99%
“…749 In 2008 Wiles published the results from a pilot trial for the CoBalT 50 study, which provided proof that they would be able to recruit the appropriate subjects for the larger HTA programme-funded CoBalT 50 RCT that followed (interviewee). 755 and an article in the British Journal of Clinical Psychiatry reflecting the findings of the nested qualitative study (interviewee).…”
Section: Appendix 44: Crash-2mentioning
confidence: 99%